Meningkatkan Kepercayaan Diri Siswa melalui Media Kartu Cerita pada Pembelajaran Berbicara - Agung, Anugrah; Amaliyah, Yuli; Ramadhani, Muhammad Habib; Yusnia; Supriatna, Irfan; Putera, Rafhi Febryan; Lestari, Eci Anita (JURIDIKDAS, 2026)
This study aims to determine the effectiveness of story card media in improving students’ self-confidence in speaking skills at the elementary school level. This research employed a pre-experimental design with a one group pretest-posttest approach. The subjects were 32 fourth-grade students of MIS Hidayatul Hasaniyyah in the even semester of the 2026 academic year. Data were collected using observation sheets of students’ self-confidence during speaking activities. The results showed that the average score of students’ self-confidence before treatment (pretest) was 45.62 and increased to 82.78 after the implementation of story card media. The improvement of 37.16 points indicates that story card media is effective in enhancing students’ self-confidence in speaking. Therefore, story card media can be used as an alternative learning medium to encourage students to express their ideas more confidently.